Clinical Characteristics of Congenital Atresia of the Left Main Coronary Artery in 12 Children - Jiang, Xiaokun; Ye, Wenqian; Xiao, Yanyan; Han, Ling; Ding, Wenhong; Li, Wenxiu; Jin, Mei; Wang, Xiaofang; Meng, Qi (Frontiers in Pediatrics, 2022)
Background: Left main coronary artery atresia (LMCAA) is an extremely rare abnormality and only less than 100 cases have been reported in the world. We describe the clinical manifestations, imaging features, prognosis and treatments of LMCAA who were admitted in our department, aimed to improve the clinical diagnosis and treatments of LMCAA in children. Methods: A retrospective study identified 12 patients diagnosed with congenital left coronary artery atresia at Pediatric Heart Center of Beijing Anzhen Hospital from June 2010 to June 2019. The clinical characteristics, imaging data and treatment follow-up were analyzed. Results: Among the 12 cases, 8 were male and 4 were female; the age of onset was 2 months to 2 years old ; the age of diagnosis was 7 months to 6 years old . At the initial diagnosis, there were 4 cases of respiratory tract infection with cardiac murmur, 3 cases of cardiac shadow enlargement, 1 case of recurrent syncope, 2 cases of feeding difficulty with cardiac enlargement, and 2 cases of simple cardiac murmur. In 12 cases of ECG examination, 7 cases showed pathological Q waves of lead I, AVL and v4-v6; in 12 cases of chest X-ray examination, 8 cases showed cardiac shadow enlargement; in 12 cases of our hospital's first cardiac ultrasound examination, 4 cases were definitely diagnosed, 8 cases showed the possibility of left coronary artery abnormality; in 5 cases of cardiac CTA examination, 2 cases were confirmed, 2 cases reported suspected left coronary artery abnormality, 1 case did not report abnormality; in 8 cases of selective contrast examination, all of them were diagnosed Clear diagnosis. Follow-up were performed from 1 to 8 years, one case died suddenly, one case of syncope after activity was cured by oral medication, three cases received open coronary angioplasty + mitral valvuloplasty, recovered well after operation, the rest of the children were treated by oral medication, and the symptoms are stable at present. Conclusions: LMCAA is difficult to diagnose and can result in heart failure early in life. Timely diagnosis and reasonable treatment are the key to improve the prognosis.